The effects of learner-generated videos for YouTube on learning outcomes and satisfaction. (April 2016) - Orús, Carlos; Barlés, María José; Belanche, Daniel; Casaló, Luis; Fraj, Elena; Gurrea, Raquel
Abstract: This paper presents the results of an educational innovation project based on learner-generated videos. The videos were created for a YouTube channel specifically developed for a marketing course. Despite the potential of YouTube as a learning tool in education, its use as a learning instrument for learner-generated content is scarce. In this project, students could voluntarily participate in the creation of videos, which were then uploaded to the channel by the professors. At the end of the course, students completed a questionnaire assessing learning outcomes and satisfaction. The findings showed that active participation had a direct influence on the perceived acquisition of cross-curricular competencies and on academic performance. While participation did not directly increase subjective learning or satisfaction with the course, it had an indirect influence through cross-curricular competencies. This research contributes to previous literature by showing how learner-generated content and the use of YouTube as a teaching vehicle has a positive impact on students' learning outcomes and satisfaction. Highlights: Learner-generated content (videos for YouTube) is promoted in higher education. Video creation improves cross-curricular competencies and academic performance. Effects on satisfaction are null and effects on subjective learning are negative. These two variables are positively affected via cross-curricular competencies. Active and experiential learning help improve students' learning and satisfaction.